3-D thermohydrodynamic analysis of textured, grooved, pocketed and hydrophobic pivoted-pad thrust bearings. (June 2017) - Zouzoulas, Vassilios; Papadopoulos, Christos I.
Abstract: In the present study, a computational investigation of thermohydrodynamic lubrication in pivoted-pad thrust bearings exhibiting different types of surface treatment is presented. Five different types of pivoted-pad thrust bearings are cross-evaluated for operation at different combinations of thrust load and rotational speed: (a) a pocket bearing, (b) a bearing with circumferential grooves, (c) a bearing with radial grooves, (d) a bearing with rectangular texturing, and (e) a hydrophobic bearing. A parametric analysis is conducted to identify the effect of the main design parameters (machining depth, radial/circumferential machining extents, slip length, radial/circumferential hydrophobic extents) on bearing performance. The performance gains obtained by each surface treatment type are evaluated against the performance of a conventional plain bearing of the same principal dimensions. Highlights: Substantiall performance improvements for textured/hydrophobic pivoted thrust bearings. Superior tribological behavior of pocket and circumferentially grooved bearings. Minimum film thickness increases up to 24% for certain textured bearings. Hydrophobicity shows great potential for load capacity increase and friction reduction.